Langerhans Cell Histiocytosis in Otorhinolaryngology - Fernandes, Humberto de Barros; Granjeiro, Ronaldo Campos; Negreiros Júnior, Jacinto de (International Archives of Otorhinolaryngology, 2009)
Introduction: The Langerhans cell histiocytosis is an inflammatory cells proliferative disorder of unknown etiology. It is uncommon disease in children. Objective: To proceed with a literature review on Langerhans cell histiocytosis, with focus on the otorhinolaryngological complications. Materials and methods: The methodology used was advised based on online data from MEDLINE, between 1966 and 2008, with research of terms related to Langerhans cell histiocytosis, temporal bones and otorhinolaryngology. Literature Review: The manifestations in the head and neck are the most common ones and their diagnosis becomes difficult once it mimetizing other more common diseases the otorhinolaryngologist sees as external ear eczema, acute mastoiditis and gingivitis. The temporal bone disease manifests as recurrent otorrhea and external auditory meatus and retroauricular granulomas. The radiological evaluation confirms lytic lesions especially in the cranial cap, jaw, temporal bones and spines. The definitive diagnosis is made by biopsy through the histopathological discoveries and immunohistochemistry detection of the CD1a antigen. The main form of treatment is by chemotherapy and, in a lower scale, radiotherapy or surgery. Conclusions: he otorhinolaryngological manifestations must be suspected for recurrent otological symptoms and the presence of retroauricular granulation tissue or and the external auditory meatus. The biopsy with characteristic histological discoveries and immunohistochemistry positive for CD1a were diagnostic. The chemotherapy may be the initial treatment in most cases or secondary in refractory or recurrent forms.